Análisis ergonómico de los equipos de protección personal que utiliza el Cuerpo de Bomberos del cantón Chone - Macias Muñoz, Dulce María (2024)
The present investigation evaluated the ergonomic risks associated with the personal protective equipment used by the workers of the Fire Department in Chone canton. The main objective was to mitigate existing risks and promote a safe work environment, thus improving the performance of operational personnel. The methods used included inductive, deductive and observational approaches, while the types of research encompassed both fieldwork and bibliographic research. Various techniques were used such as interviews and surveys. Likewise, the Liker scale tool, the SPSS program and Google Forms were used to collect relevant information that would contribute to the fulfillment of the stated objectives. It should be noted that the field instruments used were designed and validated using the Delphi method. The results obtained revealed several deficiencies within the firefighting institution, such as the lack of internal regulations, lack of knowledge of ergonomic science, the presence of ergonomic risks, absence of machinery for transporting heavy loads, and the lack of personal protective equipment suited to the individual characteristics of operational personnel. Based on these findings, an improvement plan was proposed using the 5W+1H model aimed at addressing the identified weaknesses. This plan includes the design of activities and strategies to reduce the level of ergonomic risk within the institution, promoting a safe working environment and maximizing the job performance of operational personnel, while also providing efficient protection services to the public.